Epidural esketamine and morphine for postoperative analgesia after caesarean delivery: A pilot study - Tang, Ju; Zheng, Zhiguo; Ran, Qijun; Zhao, Feng; Wang, Yao; Hu, Feng; Yang, Chao; Tan, Xiaoyong (Frontiers in Surgery, 2023)
Objective The aim of this study was to determine whether the addition of esketamine to morphine would improve postoperative analgesia after cesarean section. Methods Parturients who planned for a cesarean delivery using combined spinal–epidural anesthesia with a request for postoperative anesthesia were randomly divided into four groups (A, B, C, and D). When the surgery was completed, the parturients in groups A, B, C, and D were administered 2 mg morphine, 0.25 mg/kg of esketamine, 0.25 mg/kg of esketamine plus 2 mg morphine hydrochloride, and 0.25 mg/kg of esketamine plus 1 mg morphine through the epidural catheters, respectively. The postoperative pain at rest, pain with movement, the number of rescue analgesics, and adverse effects were evaluated for 48 h after cesarean delivery. Results A total of 119 parturients were included in this study, including 30 cases in group A, 30 cases in group B, 30 cases in group C, and 29 cases in group D. All visual analog scale (VAS) scores at rest and with movement were much lower in group C as compared with those in group A and group B (P < 0.05). Moreover, VAS scores at rest were also lower in Group C than in group D for 24 h (P < 0.05). Corresponding to the low pain scores, parturients in group C also required less rescue analgesia as compared with the other three groups (P = 0.021 for C vs. A, P < 0.001 for C vs. B, and P < 0.001 for C vs. D). There were no statistically significant differences between the four study groups with regard to the incidence of adverse events (P > 0.05). Conclusions The addition of esketamine to morphine improved postoperative analgesia after cesarean section without increasing the incidence of adverse events.